ASSISTIVE AND EDUCATIONAL TECHNOLOGIES FOR CHILDREN WITH AUTISM SPECTRUM DISORDER: A BIBLIOMETRIC STUDY - Daniele Mesquita Batista; Emilly Vasconcelos Goulart; Ana Ricelly Pereira de Oliveira; Pâmela Farias Santos; Rubenilson Caldas Valois; Maria Goreth Silva Ferreira (Cogitare Enfermagem)
Objective: To map the scientific production and create a bibliographic portfolio on developing educational and assistive technologies for children with autism spectrum disorder.